Situation Report: Hungary, 11 November 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Deputy Minister Condemns Dogmatic Stand on Crime Enterprise Profits to Exceed Last Year's Level DM Revaluation and Hungarian Foreign Trade The "Adria" Pipeline: More Effective Hungarian-Yugoslav Co-Operation New Type of Economic Co-operation in the Farmers' Co-Operatives Farmers' Co-operative Enterprise Attempts to Breach State Monopoly Study of Cattle Breeding in Italy